Functional evidence that the central renin-angiotensin system plays a role in the pressor response induced by central injection of carbachol - Saad, William A. [UNESP]; Luiz, A. C. [UNESP]; Camargo, L. A A [UNESP]; Silveira, J. E N [UNESP]; Fóglia, S. [UNESP]; Menani, José Vanderlei [UNESP] (FapUNIFESP (SciELO), 1997)
We investigated the effects of losartan, an AT 1-receptor blocker, and ramipril, a converting enzyme inhibitor, on the pressor response induced by angiotensin II (ANG II) and carbachol (a cholinergic receptor agonist). Male Holtzman rats (250-300 g) with a stainless steel cannula implanted into the lateral ventricle (LV) were used. The injection of losartan (50 nmol/l μl) into the LV blocked the pressor response induced by ANG II (12 ng/l μl) and carbachol (2 nmol/l μl). After injection of ANG II and carbachol into the LV, mean arterial pressure (MAP) increased to 31 ± 1 and 28 ± 2 mmHg, respectively. Previous injection of losartan abolished the increase in MAP induced by ANG II and carbachol into the LV (2 ± 1 and 5 ± 2 mmHg, respectively). The injection of ramipril (12 ng/l μl) prior to carbachol blocked the pressor effect of carbachol to 7 ± 3 mmHg. These results suggest an interaction between central cholinergic pathways and the angiotensinergic system in the regulation of arterial blood pressure.
Keywords: carbachol; central angiotensin; pressor response; angiotensin; losartan; losartan potassium; ramipril; animal experiment; cholinergic system; conference paper; controlled study; intracerebroventricular drug administration; male; nonhuman; rat; renin angiotensin aldosterone system; Angiotensin-Converting Enzyme Inhibitors; Animals; Blood Pressure; Carbachol; Cerebral Ventricles; Cholinergic Agonists; Losartan; Male; Pressoreceptors; Ramipril; Rats; Rats, Sprague-Dawley; Receptors, Angiotensin; Renin-Angiotensin System; Animalia